Work and migration : life and livelihoods in a globalizing world - Sørensen, Ninna Nyberg; Olwig, Karen Fog, 1948- (Routledge, 2003)
Using case studies from those who have moved either transnationally or within their own country, international contributions offer various definitions of what it means to make a living on the move.
Originally published 2002 by Routledge.
Keywords: Foreign workers.; Emigration and immigration -- Economic aspects.; Globalization -- Economic aspects.; Émigration et immigration -- Aspect économique.; Mondialisation.; Travailleurs étrangers.; globalism.; BUSINESS & ECONOMICS -- Labor.; POLITICAL SCIENCE -- Labor & Industrial Relations.; Emigration and immigration -- Economic aspects; Foreign workers; Globalization -- Economic aspects; Employment opportunities.; Migrant workers.; Rural-urban migration.; Professional workers.; Return migration.; Income sources.